2005
DOI: 10.1097/00006199-200505000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immediate Versus Delayed Pushing During Second-Stage Labor on Fetal Well-Being

Abstract: Delayed pushing results in less fetal oxygen desaturation and less > or =2-min epochs of fetal oxygen saturation <30% during second-stage labor than the immediate pushing method; thus, delayed pushing is more favorable for fetal well-being as measured by fetal oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 3 publications
3
95
0
Order By: Relevance
“…Twelve separate RCTs, [7][8][9][10][11][12]14,15,19,21,31,32 with one stratified into multiparous and primiparous women, 9 were included in the final analysis ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve separate RCTs, [7][8][9][10][11][12]14,15,19,21,31,32 with one stratified into multiparous and primiparous women, 9 were included in the final analysis ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11] Many of these studies involved small sample sizes, and their results are contradictory with regard to benefit and harm to the neonate and mother. Although some studies indicate delayed pushing reduces the duration of active pushing, 8,9,12 decreases operative delivery, 8 and minimizes maternal fatigue, 9 others found no decrease in the duration of pushing.…”
mentioning
confidence: 99%
“…They also experienced large participant attrition, which may have contributed to not comparing groups but instead reporting on the aggregate findings of incidence of urodynamic changes overall. Other studies using various pushing methods and urodynamic indices have either focused solely on women without epidurals [13]; were underpowered or had research design flaws barring conclusions [16]; or did not include pelvic floor outcomes beyond use of episiotomy for women with epidurals [17, 18]. These limitations impede understanding the implications of using varied pushing strategies and also have inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversy exists over early and late maternal pushing, delayed pushing after a period of rest probably results in a better fetal outcome. 15 Other obstetrical parameters that may affect the duration of both first-and second-stage labour include parity, maternal age, duration of the first stage, birth weight, position of the fetal head, oxytocin augmentation and epidural analgesia. 16 Schiessl et al investigated these parameters and found that in their study, the impact of epidural analgesia on the second stage of labour should be considered in obstetrical management.…”
Section: Discussionmentioning
confidence: 99%